2023
DOI: 10.1002/marc.202300251
|View full text |Cite
|
Sign up to set email alerts
|

Facile End‐Functionalization of Poly(Quinolylene‐2,3‐Methylene) Using the Terminal Palladium Complex: Thiocarbonylation through Formation of an Acyl Palladium Complex at the Polymer Terminal

Naoya Kanbayashi,
Manami Narukawa,
Kiyotaka Onitsuka

Abstract: The end‐functionalization of poly(quinolylene‐2,3‐methylene)s (PQM) via thiocarbonylation is successfully achieved by forming an acyl palladium complex. The terminal palladium complex of the PQMs synthesized by living cyclocopolymerization of o‐allenylaryl isocyanide is quantitatively converted to a tractable acyl palladium complex through the carbon monoxide insertion into a palladium–carbon bond. The resulting acyl palladium complex exhibits high reactivity toward thiols, thereby enabling the introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…We recently formed an acyl palladium complex by inserting carbon monoxide into the palladium−carbon bond of a palladium complex at the ω-chain end of a PQM (Scheme 1b). 38 The resulting acyl palladium complex was highly reactive toward thiols, thereby enabling the introduction of substituents at the ω-chain end of the PQM by effectively converting them to thioester groups. Leveraging this endfunctionalization method, we focused on the native chemical ligation (NCL) technique, 39 which is widely employed in peptide synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We recently formed an acyl palladium complex by inserting carbon monoxide into the palladium−carbon bond of a palladium complex at the ω-chain end of a PQM (Scheme 1b). 38 The resulting acyl palladium complex was highly reactive toward thiols, thereby enabling the introduction of substituents at the ω-chain end of the PQM by effectively converting them to thioester groups. Leveraging this endfunctionalization method, we focused on the native chemical ligation (NCL) technique, 39 which is widely employed in peptide synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we designed a bifunctional monomer containing isocyano and allenyl groups at adjacent positions on the benzene ring and revealed that cyclocopolymerization proceeds in the presence of an organopalladium complex through completely alternating insertions of isocyanide and allene moieties into the palladium–carbon bonds with perfect head-to-tail selectivity to produce a novel polymer backbone: poly­(quinolylene-2,3-methylene)­s (Scheme b-1) . Furthermore, by selecting the appropriate ligand, cyclocopolymerization can be expanded to living polymerization, which enables precise control of the molar mass and end structure of the resulting polymer. , Additionally, the unique polymer backbone exhibits the formation of specific helical structures , and associated physical properties . These findings are anticipated to propel further advancements and progress in the field of cyclopolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…21 tion can be expanded to living polymerization, 24 which enables precise control of the molar mass and end structure of the resulting polymer. 25,26 Additionally, the unique polymer backbone exhibits the formation of specific helical structures 27,28 and associated physical properties. 29 These findings are anticipated to propel further advancements and progress in the field of cyclopolymerization.…”
Section: ■ Introductionmentioning
confidence: 99%